Implementasi Reformasi Sistem Kafala terhadap Upaya Perlindungan Hak Asasi Manusia Buruh Migran di Qatar - Oneson, Samuel Ransi; Mamma, Beche Bt. (Universitas Bosowa, 2024)
During the construction of World Cup 2022 infrastructures in Qatar there assumed to be human rights violations against migrant workers. Around 1200 migrant workers died between the year of 2010-2014 because of forced labor, bad environment, withholding wages, limited access to proper health care, discriminatory and exploitative treatment. This paper aims to describe the failure Kafala system which argued to enable the exploitation or violation of human rights against migrant workers by using qualitative research methods. The results of this study show that Qatar as an actor who responsible to secure the human rights of migrant workers has not succeeded in making a proper policy as a solution to the human rights violations that have occurred and instead created new problems from its attempt to reform the policy. Second, the gulf countries do not want to abolish the Kafala system and require its implementation because migrant workers make a major contribution to the development of their countries. Third, FIFA failed to become a law enforcer for Qatar because in organizing mega sport events, FIFA and the host country should have respected applicable laws and international principles related to human rights, including the concept in the UNGPs namely protect, repair and respect.